(untitled) (Fiep Bulletin - online, 2011)
Objectifying to verify the influence of the physical activity in the health and well-being of the aged ones, this research of quantitative matrix has the intention to analyze the data caught through a closed questionnaire, with 12 questions that aim to perceive the physical, social and psychological changes in the life of the aged ones. The sample possesses 18 participants with average age superior to 60 years old. The research was done in the Society, Firemen and Health Project, located in Jacarecanga neighborhood Fortaleza, Ceará, inside the headquarters of General Command of the Military Body of Firemen. The activities in the project happens 3 times a week in the morning and are headed by firemen graduated in Physical Education. It was evidenced with this research the perception of physical and psychological improvements on the part of the Aged one with regular practice of physical activities.